High Sulfation and a High Molecular Weight Are Important for Anti-hepcidin Activity of Heparin - Asperti, Michela; Naggi, Annamaria; Esposito, Emiliano; Ruzzenenti, Paola; Di Somma, Margherita; Gryzik, Magdalena; Arosio, Paolo; Poli, Maura (Frontiers in Pharmacology, 2016)
Heparins are efficient inhibitors of hepcidin expression even in vivo, where they induce an increase of systemic iron availability. Heparins seem to act by interfering with BMP6 signaling pathways that control the expression of liver hepcidin, causing the suppression of SMAD1/5/8 phosphorylation. The anti-hepcidin activity persists also when the heparin anticoagulant property is abolished or reduced by chemical reactions of oxidation/reduction (glycol-split, Gs-Heparins) or by high sulfation (SS-Heparins), but the structural characteristics needed to optimize this inhibitory activity have not been studied in detail. To this aim we analyzed three different heparins (Mucosal Heparin, the Glycol split RO-82, the partially desulfated glycol-split RO-68 and the oversulfated SSLMWH) and separated them in fractions of molecular weight in the range 4-16 kD. Since the distribution of the negative charges in heparins contributes to the activity, we produced 2-O- and 6-O-desulfated heparins. These derivatives were analyzed for the capacity to inhibit hepcidin expression in hepatic HepG2 cells, in mice, and also for the capacity to bind an Heparin Binding Domain peptide. The three approaches produced consistent results and showed that the anti-hepcidin activity strongly decreases with molecular weight below 7 kD, with an increase of the N-acetylation level and after 2-O and 6-O desulfation. The high sulfation and high molecular weight properties for efficient anti-hepcidin activity suggest that heparin is involved in multiple binding sites.